1984
DOI: 10.1017/s0025315400030204
|View full text |Cite
|
Sign up to set email alerts
|

Food resource, gametogenesis and growth of Mytilus edulis on the shore and in suspended culture: Killary Harbour, Ireland

Abstract: Mussels, Mytilus edulis L. grow on the shore and are cultured on ropes in Killary Harbour, a fjordic inlet on the Irish west coast. The food resource available to cultured mussels differs from that available to wild mussels on the shore. Although phytoplankton densities as estimated from chlorophyll a concentrations are similar, the shore environment in the inner part of the inlet is characterized by high mean POC concentrations. This is because of the presence of variable amounts of allochthonous detrital car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
86
3
5

Year Published

1994
1994
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(100 citation statements)
references
References 25 publications
6
86
3
5
Order By: Relevance
“…The growth rates measured in the present study, ranging from 6.3 to 11.1 mm month -1 , were slightly higher than those reported by Perez Camacho and Roman (1979) for mussels from the Ria de Arousa, comparable or occasionally higher than those reported by Page and Hubbard (1987) for Californian Mytilus edulis, which were considered by the authors as 'among the highest rates recorded world-wide', and markedly higher than those measured for this species by Rodhouse et al (1984) in Ireland. These growth rates are also greater than the growth rates of mussels cultured in intertidal areas, for either M. edulis (Theisen, 1968;Lube& 1969;Rodhouse et al, 1984;Hager, 1970) or the Mediterranean Mytilus galloprovincialis (Ceccherelli and Rossi, 1984).…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…The growth rates measured in the present study, ranging from 6.3 to 11.1 mm month -1 , were slightly higher than those reported by Perez Camacho and Roman (1979) for mussels from the Ria de Arousa, comparable or occasionally higher than those reported by Page and Hubbard (1987) for Californian Mytilus edulis, which were considered by the authors as 'among the highest rates recorded world-wide', and markedly higher than those measured for this species by Rodhouse et al (1984) in Ireland. These growth rates are also greater than the growth rates of mussels cultured in intertidal areas, for either M. edulis (Theisen, 1968;Lube& 1969;Rodhouse et al, 1984;Hager, 1970) or the Mediterranean Mytilus galloprovincialis (Ceccherelli and Rossi, 1984).…”
Section: Discussioncontrasting
confidence: 66%
“…These growth rates are also greater than the growth rates of mussels cultured in intertidal areas, for either M. edulis (Theisen, 1968;Lube& 1969;Rodhouse et al, 1984;Hager, 1970) or the Mediterranean Mytilus galloprovincialis (Ceccherelli and Rossi, 1984).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Rodhouse et al (1984) found annual dr,/weights in 30 mm mussels in England between 85 and 200 mg, which corresponds to a condition index of 3.1-7.4. In contrary, condition indexes even lower than those found in the present study are possible.…”
Section: Discussionmentioning
confidence: 92%
“…For suspended culture methods, such as the deployed longlines, mussels feed continuously and therefore grow rapidly (Seed 1968a, b). Water depth can be a limiting factor in tidal seas as usually a minimum water column height is essential during the low water spring tides due to variations in food availability within the water column (Rodhouse et al 1984;Page and Hubbard 1987). At the site Nordergründe, we suggest to submerge the longline at least 6-7 m to avoid the energy forces from waves.…”
Section: Depth and Aerial Exposurementioning
confidence: 99%